2020
DOI: 10.1007/s12144-020-00887-x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring hope during the COVID-19 outbreak in the Philippines: development and validation of the state locus-of-Hope scale short form in Filipino

Abstract: Various adaptations of the Dispositional Hope Scale have been validated and used for specific research and applied purposes. The Locus-of-Hope Scale was developed as a cultural adaptation that measures internal and external aspects of agency related to goalpursuit that are typical in collectivist cultures. The scale has been used to account for variations in well-being-related factors in collectivist societies but still assumes that hope-related thoughts are dispositional. A State Locus-of-Hope Scale was devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 46 publications
2
30
0
1
Order By: Relevance
“… Respondents highlighted the risk of infecting self or colleagues or family members and lack of protective gear at the work‐place as leading causes of stress. 27 Measuring hope during the COVID-19 outbreak in the Philippines: development and validation of the state locus-of-Hope scale short form in Filipino ( Bernardo & Mendoza, 2020 ) General population; n = 3182; Online survey; Cross-sectional study Hope; anxiety; psychometric properties Confirmatory factor analysis showed a good fit between the four-factor model (as opposed to one-factor and two-factor models), supporting the scale’s structural validity. There was also good evidence for the subscales’ convergent and discriminant validity.…”
Section: Resultsmentioning
confidence: 96%
“… Respondents highlighted the risk of infecting self or colleagues or family members and lack of protective gear at the work‐place as leading causes of stress. 27 Measuring hope during the COVID-19 outbreak in the Philippines: development and validation of the state locus-of-Hope scale short form in Filipino ( Bernardo & Mendoza, 2020 ) General population; n = 3182; Online survey; Cross-sectional study Hope; anxiety; psychometric properties Confirmatory factor analysis showed a good fit between the four-factor model (as opposed to one-factor and two-factor models), supporting the scale’s structural validity. There was also good evidence for the subscales’ convergent and discriminant validity.…”
Section: Resultsmentioning
confidence: 96%
“…The evidence so far is that external locus-of-hope dimensions predict measures of coping ( 36 , 37 ) and well-being in adolescents ( 38 , 39 ), university students ( 40 ), and adults ( 41 ). One recent study found consistently negative associations between external locus-of-hope dimensions and anxiety during the COVID-19 pandemic ( 42 ). But no prior research has investigated how external locus-of-hope moderates the relationship between perceived stress and mental health (i.e., depression, anxiety) or physical health (i.e., sleep quality), although there is some research on the buffering effect of external locus-of-hope on stressors and positive psychological outcome ( 43 , 44 ).…”
Section: Introductionmentioning
confidence: 99%
“…As our sample was not a nationally representative one, we should not interpret that as a national prevalence rate. But the ratio of participants experience anxiety using CPAS-11 is higher than the 13.84% identified as experiencing severe anxiety using GAD-7, which has been used to measure anxiety of Filipinos during the COVID-19 pandemic in at least one previous study (Bernardo & Mendoza, 2020). The ratio is also higher than the 11.07% of the respondents experienced severe to extremely severe anxiety using the anxiety subscale of the Depression, Anxiety, and Stress Scale (DASS-21;Lovibond & Lovibond, 1995) in another study (Tee et al, 2020) involving a Filipino sample.…”
Section: Discussionmentioning
confidence: 99%